PRELIMINARY STUDIES ON THE ELECTRICAL CONDUCTANCE AND THE VISCOSITY OF SOME NIGERIAN TRADITIONAL SOAPS IN AQUEOUS SOLUTION (Biological Sciences - PJSIR, 2001)
The viscosity and electrical conductance of some Nigerian traditional soaps and their separate mixtures with sodium chlorideand calcium chloride have been examined. The activation energies of viscous flow and of electrical conductance wereevaluated from viscous and conductance data respectively. Results on viscous flow suggest structural similarities between thesoaps examined. The halides used enhanced the electrical conductance ofthe soaps in solution and hence the halides can beused to dope the conducting ability of the soaps. The soap solution thus doped could be used industrially as electrolyte, aneconomic use to which the soaps has not been put hitherto,